ANALISIS FAKTOR-FAKTOR KELELAHAN KERJA PADA PENGEMUDI TRANSPORTASI DARAT - Yulizar Sukma Rani; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Work fatigue is a problem in the field of occupational safety and health (K3) in Indonesia which is also a risk factor for work accidents, one of which is a traffic accident. One of the body's responses and reactions to psychosocial stress that is experienced at a certain time is a feeling of fatigue. Work fatigue is not only physical or psychological, work fatigue is also related to decreased physical performance, the emergence of fatigue, decreased motivation and work productivity.Method: data collection using review literature collected from Google Scholar. Purpose: To find out what factors cause work fatigue in land transportation drivers. Results: There is a relationship between the variable factors that cause work fatigue in land transportation drivers